Especiação química de ferro em tomates utilizando um analisador automático FBA e imagens digitais - Rodrigues, Andreia Rufino (2018)
This study proposes a new automatic methodology for the chemical speciation of iron in tomato samples using an automatic batch flow analyzer. The automatic analyzer was equipped with a webcam as a sensor for acquisition of digital images according to the RGB color system. The method for the determination of iron (II) is based on the reaction of iron with 1,10phenanthroline which forms an orange complex with maximum energy absorption at 510 nm. Total iron is determined by reducing iron (III) to iron (II) with ascorbic acid, and them iron (III) is quantified by the difference between total iron and iron (II) amounts. To validate the methodology, analyzes were done using certified reference material (NIST 1547). The linear models of the analytical curves were validated by means of ANOVA, and the graphic analysis of the residuals left by the models. The analytical frequency was 94 h-1, with relative errors between 1.1% and 2.5% and deviations between 0.1% and 0.41%. The analysis time of each sample was estimated at 38 s for both iron (II) and total iron determination. The combined sample and reagent consumption in each analysis were around 0.54 mL and 0.66 mL respectively. The LOD and LOQ values were 2.33 and 7.72 μ L-1 respectively. The iron contents found in the samples ranged from 0.54 and 2.53 mg L-1. The determination of iron (II) and total iron were corroborated by reference methods, respectively, molecular absorption in UV / Vis and ICP-OES. It was observed that there was no statistically significant difference between the results, applying the t-paired test at the 95% confidence level. The proposed FBA system proved to be a useful tool for the determination of the analytes studied.